Fiqh Siyasah terhadap Implementasi Pasal 87 UU BUMDes: Optimalisasi Ekonomi Desa Sadar Sriwijaya - Kanaya, Aulia Najwa; Firdawaty, Linda; Santoso, Rudi (Legal Standing : Jurnal Ilmu Hukum, 2025)
BUMDes as a source of Village Original Income is a business entity managed by a group of people who are entrusted by the Village Council to improve the village economy and explore its potential systematically for mutual benefit. Village-Owned Business Entities aim to optimize the economy of village residents by building villages and business entities. The purpose of this research is to identify how Article 87 of the BUMDes Law can be utilized to optimize the village economy. The formulation of the problem in this research is the position of the Sadar Sriwijaya Village Government in implementing Article 87 of the BUMDes Law to optimize the village economy, and the use of Fiqh Siyasah analysis in this regard. This research uses a qualitative descriptive method in the field, with information collection through observation, interviews, and recording. Based on the results of the study, the economy of Sadar Sriwijaya Village has been running well, but has not been running optimally due to limited business capital and less than optimal dependence on PAD. In other words, there has been no business development cooperation between BUMDes and villagers.